Directions of Development Ground-Level Processing Plugs (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In Uzbekistan, cotton and its accompanying crops are cultivated in specific soil and climatic conditions. The article analyzes the technologies and design features of plows for basic tillage of the cotton-growing zone. A combined frontal plow for smooth, rowless plowing is proposed. The devices and the principle of operation of the plow are given. It has been found that when using a frontal plow, direct costs per hectare are reduced by 55-60% compared to the existing technology, and fuel consumption by 57-60%.